142 Effects of Dam Parity on Prenatal Beef Calf Nutrient Availability. (10th April 2018) - Duncan, N B; Stoecklein, K S; Meyer, A M
Abstract: We previously reported that dam parity impacts neonatal calf metabolic status. Our current objectives were to determine the effect of dam parity on prenatal calf nutrient availability assessed through placental size, fetal growth (calf size at birth), calf vigor, and 0 h circulating energy and protein metabolites. Pregnant dams were managed similarly in late gestation, then moved to dry lots (d 266 of gestation) and fed ad libitum tall fescue hay (6.7% CP and 63.9% NDF, DM basis) and 1.0 kg DM/d DDGS. Neonatal calves from multiparous (n = 36; parity = 4.3 ± 0.4 [SE]; prepartum BW = 663 ± 11 kg; BCS = 5.2 ± 0.1; gestation length = 275.4 ± 0.5 d; 21 bull and 15 heifer calves) and primiparous (n = 18; BW = 552 ± 15 kg; BCS = 5.0 ± 0.1; gestation length = 276.1 ± 0.8 d; 7 bull and 11 heifer calves) dams were monitored for time to stand and vigor score at 10 min of age (scored 1 = very weak to 5 = extremely vigorous). Calf weight and body size (shoulder to tailhead length, heart girth, abdominal girth, and cannon circumference) were measured at 20 ± 15 h of age. Ponderal index was calculated as birth weight (kg)/length (cm) 3 . Calf jugular blood samples were obtained at 0 h (pre-suckling but post-standing) and analyzed for serum glucose, blood urea nitrogen, creatinine, albumin, total protein, and globulin. Expelled placentas were collected, rinsed, dissected to determine cotyledon number, and dried to determine dry weight. Data were analyzed using a mixed model containing the effect of parity. Calf sex was included in the model for body size measurements when P < 0.25. Placentas from multiparous dams tended to have greater ( P ≤ 0.08) whole placental and inter-cotyledonary weight. Calves from multiparous dams weighed more ( P = 0.04) and had greater ( P = 0.006) abdominal girth at birth. Serum creatinine at 0 h was greater ( P = 0.047) in calves from primiparous than multiparous dams. All other energy and protein metabolites were not different ( P ≥ 0.17) between parities. Additionally, parity did not affect ( P ≥ 0.70) calf vigor. These results indicate that fetal growth and whole placental weights are likely affected by dam parity. However, because most 0 h energy and protein metabolites were not affected by parity, its influence on calf nutrient availability may be more evident earlier in gestation than at birth.